Application of Media Booklet to Improve Language Development (initial reading) on Children in Kindergarten Kemala Group B Bhayangkari 34 Kendal - Sari, Desi Karunia; Handayani, Sri Sri Sularti Dewanti; Tasuah, Neneng (Universitas Negeri Semarang, 2017)
This research aims to determine differences in the results of improvement in early reading skills of children through the use of media booklet. Sample was taken using purposive sampling taken in kindergarten Kemala Bhayangkari 34 Kendal in B age group 5-6 years. This study used an experimental method Pre-experimental design with the kind of one group pretest posttest design. Collecting data in this study using the method of observation and documentation. The study is divided into 14 sessions (1 time pretest, 12 times of treatment and continued 1 times posttest).The data were analyzed using statistical quantitative analysis methods. The results showed an increase in children's early reading skills in group B with the following details: amounting to 81.82% of children have the ability to bring the beginning of the category as well as 18.18% of the children had a very good early reading skills. Based on statistical calculations get that tcount> ttable, where t-value (+). If the worth (-) then converted mathematically, results were obtained with t-value of -36.516 great while ttable is -2.0369. It can be concluded that Ho rejected and Ha accepted, it means that there are differences in children's early reading skills after using the booklet.